2022
DOI: 10.1186/s12961-022-00832-3
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-sweetened beverage tax implementation processes: results of a scoping review

Abstract: Taxing sugar-sweetened beverages (SSB) is seen as a win–win situation for governments. It is argued that SSB taxes are relatively easy to implement from a practical perspective compared to for example other nutrition policies. However, the implementation of SSB taxation laws does not happen by itself. Therefore, this work examines implementation processes for SSB taxation in terms of (1) pre-implementation context, (2) taxation instruments used and (3) interactions in the implementation process. Ten databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 73 publications
(124 reference statements)
0
12
0
Order By: Relevance
“…The widespread implementation of the Nutri Score system, due to the ease of data interpretation, may contribute to the improvement of nutritional knowledge [ 19 ]. Moreover, taxes on unhealthy food should be extended [ 42 ]. In 2021, Poland implemented a sugar tax [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The widespread implementation of the Nutri Score system, due to the ease of data interpretation, may contribute to the improvement of nutritional knowledge [ 19 ]. Moreover, taxes on unhealthy food should be extended [ 42 ]. In 2021, Poland implemented a sugar tax [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, taxes on unhealthy food should be extended [ 42 ]. In 2021, Poland implemented a sugar tax [ 42 ]. Preliminary findings showed that the implementation of sugar tax improved population diets [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To depict the flow of information through the different phases of the scoping review, we used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis: Extension for Scoping Reviews (PRISMA-SCR and flowchart). 24 A study protocol was published beforehand with Open Science Framework. 25…”
Section: Methodsmentioning
confidence: 99%
“…Due to the small number of available studies, these two scoping maps did not allow firm conclusions about processes. 45 It seems, however, that implementation of active design guidelines in planning and whole-of-city approaches are characterized by a coordinative approach, whereby implementation of national physical activity guidelines is a mix of different processes.…”
Section: Public Policies With Potential Influence On Food and Physica...mentioning
confidence: 99%